Computational Modeling of Water Droplets Under Cooling and Freezing Conditions - Meireles, Rúben D. S. O. (2022)
The crystallization of water droplets is a ubiquitous phenomenon, which plays afundamental role in many natural and artificial processes. This phenomenon gainedparticular interest in the aeronautical industry due to ice accretion on lifting surfaces andengine intakes. A performance study is made of several models for predicting cooling and freezing phenomena, ranging from one- and two-way coupling to full-fledged four-stage freezing methodologies. First, a performance study is made of the one- and two-way coupling methodologies in the portrayal of the interaction of the particles and the surrounding gas on free-falling water droplets with diameters ranging from 3 to 6 mm and relative humidity ratios of 0.29, 0.36. 0.52 and 1.00. Then a generalized four-stage freezing model is implemented, where the temperature evolution of a suspended water droplet is tracked, adding to the cooling in the free-falling conditions, the recalescence and solidification stages. The results indicate that, for high relative humidity ratio, the interaction particles-medium is preponderant and needs to be accounted for, which does not take place for low relative humidity ratios, where one-way coupling seems to be suitable approximation. Lastly, the full stage freezing model was able to capture the experimental trend of recalescence and solidification stages.